دور عائلة بني حمدون في تثبيت أركان دولة الفاطميين بالمغرب - مسعودي, نورالدين (جامعة الوادي - University of Eloued, 2019)
This research includes a study on the role played by the Bani Hamdoun family in the dissemination of the Ismaili da'wa in the Maghreb and its great contribution to the consolidation of the foundations of the Fatimid state in Maghreb. In order to reveal this family, we have divided this study into four elements.We discussed in the first; the origin and proportions of Bani Hamdoun, and touched on the history of the family , its doctrine and the beginning of its presence in the Maghreb, In the second element, we discussed the state of Bani Hamdun in M’sila and al-Zab territory . The third element dealt with the Bani Hamdoun stand against the opponents of the Fatimid state. The fourth and last element deals with the defeat of Bani Hamdoun.
مقال
Keywords: بني حمدون؛ الفاطميين؛ المغرب؛ الأندلس